Endurantism and Spatio-Temporal Extension; [Endurantismo y Extensión Espacio-Temporal] - Rossi-Fernandez, C (Universidad Nacional de Colombia, 2024)
According to the extended characterization of the debate between endurantists and perdurantists, material objects persist temporally either by virtue of being fully present at different moments in time, or by virtue of possessing temporal parts at different moments in time. The present paper sets out to make a defense of the endurantist theory from the objections raised by Barker and Dowe (2003; 2005) and Hofweber and Velleman (2011). Those objections attempt to show that Endurantism (i) logically assumes the characteristic thesis of perdurantist theory and (ii) is internally inconsistent. Against these objections, I argue that at least in some of its versions, Endurantist theory is perfectly coherent and assumes no commitment to the existence of temporal parts. © 2024 Universidad Nacional de Colombia. All rights reserved.